COMMUNICATIVE FUNCTIONS OF PREPOSITIONAL PHRASES IN THE PREDICATIVE POSITION: FROM GRAMMAR TO PRAGMATICS (Modern American Journal of Linguistics, Education, and Pedagogy, 2025)
This article explores the communicative functions of prepositional phrases (PPs) when used in the predicative position, bridging the domains of syntax, semantics, and pragmatics. While traditional grammar often treats PPs as peripheral modifiers, their role in predicate structures reveals significant implications for meaning-making and discourse function. This paper analyzes how PPs convey locative, temporal, modal, and evaluative meanings in English, focusing on both their grammatical behavior and pragmatic functions in authentic discourse. The study employs a corpus-based method, supported by functional grammar and speech act theory, to illustrate how prepositional predicates contribute to contextual relevance, speaker stance, and information structuring. Ultimately, this research affirms that PPs in the predicative slot serve dynamic communicative purposes, challenging static views of grammatical roles.